Design for Sustainable Fabrication - Mei, Yuxuan (My University, 2025)
Design tools play a crucial role in how effectively the advances in manufacturing can be utilized to create products of unprecedented complexity. The usability of these tools directly impacts who can design, customize, and ultimately enhance the performance of products. Meanwhile, the revolution in manufacturing is fundamentally changing what can be made and by whom, enabling on-demand production of complex and functional objects. Despite its ever-increasing potential, manufacturing continues to consume considerable natural resources and produce significant amounts of waste and carbon emissions. This raises a critical research question: how can we foster sustainable fabrication practices in this rapidly evolving landscape? In this dissertation, we address the challenge by developing computational design systems that make it easier for users to create sustainable designs, thereby reducing material usage and waste at the source. Our approach centers on creating domain-specific abstractions for design systems that enable more effective exploration of the design space considering sustainability and expression of users’ design intent. We show how this approach can be applied to various fabrication domains, including electronics, home accessories, and textiles, and discuss future work directions and potential impact beyond fabrication.
Thesis (Ph.D.)--University of Washington, 2025
Keywords: computational design; computer graphics; fabrication; sustainability; Computer science; Computer science and engineering